Banking innovations and their influence on the formation of digital banking - Dziamulych, Mykola; Stashchuk, Olena; Korobchuk, Tetiana; Mostovenko, Nataliia; Martyniuk, Rostyslav; Strelkova, Iulia; Grebeniuk, Nadiia (Magnanimitas AG, 2021)
The article considers the peculiarities of the influence of banking innovations on the transformation of banking into a digital banking system. Definitelyfeatures of digitalization of banking services and models of digital banking. The necessity of involving banking institutions in the intensive introduction of the latest digital technologies in their activities to increase their own competitive position and increase the bank's profitability has been proved. A set of measures to increase the efficiency of digital technology implementation in banking is proposed
Keywords: banking innovations; banking operations; digital banking; digital banking products; Internet banking